Pengaruh Penerapan Model Problem Based Learning (PBL) dalam Pembelajaran IPS terhadap Kemampuan Berpikir Tingkat Tinggi (HOTS) pada Siswa Sekolah Dasar - Annisa Dwi Hamdani; Najwa Nurhafsah; Tin Rustini (Journal on Education, 2022)
The world of education has challenges to improve superior and quality human resources by building 21st century skills which include 1) creative thinking, 2) critical thinking and problem solving, 3) communication, and 4) collaboration. One of the skills that must be developed in every implementation of learning activities is higher order thinking skills (HOTS). This study aims to describe the effect of the student's Problem Based Learning (PBL) model in social studies learning on students' higher-order thinking skills. The type of research used in this study is a literature study method with a qualitative approach. Data collection techniques by collecting as much information as possible from various literature sources related to Problem Based Learning and higher order thinking skills or HOTS. The results of the study indicate that there is an effect of the PBL model in making students active, independent, and able to think at higher levels. In the Problem Based Learning (PBL) model, students are taught to apply new knowledge to solve problems, so that students become critical, independent and creative thinking.